Pengarusutamaan Sustainable Development Goals (SDGS) Program Pengentasan Kemiskinan di Kota Pagar Alam - Ricky Rachmatullah; Teguh Endaryanto; M Irfan Affandi (Diponegoro University, 2021)
Poverty is one of the indicators in judging the succeded sustainable development efforts. This study aims to analyze correlation between poverty alleviation budget programs by the Government and Local Government of Pagar Alam City with the percentage of poverty levels and determine poverty alleviation priority programs can be pursued by the Local Government of Pagar Alam City related to the achievement of SDGs mainstreaming target on 2030. The analytical method in this study uses the Pearson Correlation and Analytical Hierarchy Process (AHP). The results showed that the poverty allevation program budget had a signifiant corelation to the poverty percentage reduction in collaborative and synergistic budgeting through the APBD of Pagar Alam with APBN. Based on the assessment in the AHP model, the Social Welfare Services and Rehabilitation Program is first ranked or the first choice in the framework of poverty alleviation by SDGs mainstreaming.